An efficient multi-functional material based on polyether-substituted indolocarbazole for perovskite solar cells and solution-processed non-doped OLEDs. Issue 4 (7th January 2019) - Mai, Runsheng; Wu, Xiayan; Jiang, Yue; Meng, Yuying; Liu, Baiquan; Hu, Xiaowen; Roncali, Jean; Zhou, Guofu; Liu, Jun-Ming; Kempa, Krzysztof; Gao, Jinwei
Abstract : A multi-functional material is demonstrated, and it simultaneously improves the efficiency of PSCs and emits bright light for solution-processed non-doped OLEDs. Abstract : We demonstrated an efficient multi-functional material, ( E )-1, 2-bis(5, 11-bis(2-(2-ethoxyethoxy)ethyl)-5, 11-dihydroindolo[3, 2- b ]carbazol-2-yl)ethane (BEDCE ), obtained by a simple and low-cost solution processing procedure, which can be used as both an interfacial layer in perovskite solar cells (PSCs) and a greenish-yellow light emitter in organic light-emitting diodes (OLEDs). With excellent morphology and interfacial contact due to its elastomeric and amphiphilic properties, theBEDCE layer at the perovskite/Spiro-OMeTAD interface in PSCs significantly improves the short-circuit current and fill factor, enhancing the efficiency from 17.20% to 19.02%. Besides, the first solution-processed non-doped greenish-yellow OLEDs based on elastomericBEDCE show efficiency and luminance of 4.56 cd A −1 and 10 320 cd m −2, respectively, which are among the highest performances. Thus, to the best of our knowledge, BEDCE is the first multi-functional material to be utilized in both OLEDs and PSCs with good performances, showing its promising potential applications for various devices.